Reflections on Three Different High School Chemistry Lab Formats during COVID-19 Remote Learning - Kelley, Elizabeth W (Journal of chemical education, 2020)
Due to the COVID-19 pandemic, education at all levels has temporarily shifted to remote learning, hobbling an integral component of chemistry courses: the laboratory. The chemistry lab is crucial for developing student engagement and learning with hands-on, relevant experiments in a socially dynamic classroom setting. The transition to remote learning consequently presents additional obstacles for chemistry educators and students, supplemental to challenges experienced by all disciplines. This article conveys preliminary indications about various remote learning laboratory scenarios by comparing three different formats for high school chemistry laboratories from the 2020 spring semester, with the aim of informing preparations for hands-on laboratory instruction in the fall. The results tentatively support that hands-on laboratory instruction should ideally occur in the classroom or, if necessary, by sending home all requisite supplies in order to promote effective, equitable learning, engagement, and performance.